Senior Living Space Architecture Design based on Iot Devices Using Vital Sensors - Jae Lim, Myung; Yeon Park, Soh; Man Kwon, Young; Kun Chung, Dong; ., . (International Journal of Engineering and Technology, 2018)
This paper seeks to propose a senior living lab prototype based on the Internet of Things (IoT). Currently, IoT research is actively being conducted in various fields, and the field of IoT healthcare for elderly people is being highlighted with a rapid growth of ageing population. In this paper, a living lab platform was designed to recognize the movements of elderly people in real time and measure the quantity of motion by using Arduino's ultrasonic sensors and to help maintain a comfortable environment by using temperature & humidity sensors, which complemented the shortcomings of living lab based on the IoT healthcare.Â